Features of magneto-optics of dichroic cholesteric liquid crystals - A.H. Gevorgyan; S.S. Golik (Компьютерная оптика, 2021)
In this work, magneto-optical properties of a dichroic cholesteric liquid-crystal layer are theoretically investigated at large values of the magneto-optical parameter. Features of all solutions of the dispersion equation are studied in detail. Peculiarities of the reflection, transmission, absorption spectra and the influence of dielectric boundaries on them are investigated. Specific properties of the localization of light and magnetically induced transparency in dichroic cholesteric liquid crystals are considered. The study of the light localization features showed that the presence of an external magnetic field, as well as the presence of dielectric boundaries, led to the appearance of oscillations in the dependence of the intensity of the layer-confined energy on the coordinate of the axis directed along the cholesteric axis. A strong influence of the refractive index of isotropic half-spaces adjacent to a dichroic cholesteric liquid crystal layer on the optics of the layer under consideration is shown. In particular, magnetically induced transparency and diffraction transmission appear only at certain intervals of the refractive index of isotropic half-spaces.